788 Caecal Duplication Cyst: An Unexpected Cause of Bowel Obstruction in a 12-Year-Old. (19th August 2022) - Dale, J; Mclean, E; Gupta, T; Healy, C
Abstract: We report the case of a rare cause of bowel obstruction in a 12-year-old girl who presented with a short history of abdominal distension and vomiting after a month of unexplained urinary frequency and weight loss. Abdominal radiographs demonstrated small bowel obstruction with an unknown pelvic mass. A raised CA125 suggested a possible ovarian lesion and a magnetic resonance scan was interpreted as supportive of this pathology. Intra-operatively a 120x90x70mm cystic mass was found attached to the caecal serosa, immediately adjacent to the ileocaecal valve. There was an associated 180-degree twist of the terminal ileum and ascending colon. A limited right hemicolectomy was performed, and histopathology confirmed the diagnosis of a caecal intestinal duplication cyst. Post-operatively she has recovered well, with resolution of her obstructive and urinary symptoms. Given the unusual age of presentation, uncommon location of the cyst and the diagnostic challenges incurred, the authors wish to share their experience of managing an atypical duplication cyst.